ESG, Kepemilikan Institusional, dan Nilai Perusahaan: Peran Mediasi Kinerja Perusahaan - Asyifa, Farhan; Safitri, Julia; Gusni (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effect of Environmental, Social, and Governance (ESG) and institutional ownership on firm value with corporate performance as a mediating variable in companies listed on the IDX ESG Leaders index during the 2020-2024 period. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) on 85 observations from 17 companies, this study tested seven hypotheses. The results show that ESG has no effect on either corporate performance or firm value. Conversely, institutional ownership positively affects both corporate performance and firm value. Corporate performance partially mediates the relationship between institutional ownership and firm value, but does not mediate the ESG-firm value relationship. These findings indicate that institutional ownership plays a strategic role as a value driver through dual pathways, while ESG effectiveness in creating value still requires strengthened signal credibility and market understanding.